Simultaneous occurrence of two distinct histotypes of ovarian endometriosis-associated cancer in bilateral ovaries: implications for monoclonal histogenesis from a case report - Zhao, Luyang; Liu, Yunyue; Liu, Feng; Jin, Xiangshu; Xu, Jia; Zhou, Shuting; Meng, Yuanguang; Liu, Aijun; Yang, Weng (Frontiers in Oncology, 2023)
Background: Transformation of endometriosis to malignancy is a rare occurrence. Clear cell ovarian cancer and endometrioid ovarian cancer are the two histotypes most consistently linked to endometriosis. The exact pathways leading to malignant transformation of endometriosis remain elusive. Case presentation: A 41-year-old woman presented to our hospital with a ten days history of abdominal pain which was not responsive to medication. Pathological examination revealed an unexpected finding of bilateral endometriosis associated with distinct malignancies: a clear cell carcinoma in the right ovary and a well-differentiated endometrioid carcinoma in the left ovary. Molecular analysis indicated a shared somatic driver mutation in ING1 in the eutopic endometrium and the bilateral ovaries while simultaneously exhibiting specific genetic alterations unique to each carcinoma. Notably, several common mutation sites were also identified, including previously reported common oncogenes (KRAS, PIK3CA, ARID1A). This finding prompts the hypothesis of a possible monoclonal origin of the two tumours. Conclusion: This case represents an exceedingly rare occurrence of two different histotypes of ovarian endometriosis-associated cancer manifesting simultaneously in bilateral ovaries. Based on genetic analysis, we hypothesize that these malignancies may have a monoclonal origin, providing insights into understanding the different biological mechanisms underlying carcinogenesis.